2011
DOI: 10.1186/1476-9255-8-17
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-inflammatory and anti-coagulant effects of antibiotics towards Platelet Activating Factor and thrombin

Abstract: BackgroundSepsis is characterized as a systemic inflammatory response that results from the inability of the immune system to limit bacterial spread during an ongoing infection. In this condition the significant mediator of inflammation Platelet Activating Factor (PAF) and the coagulant factor thrombin are implicated. In animal models, treatment with PAF-antagonists or co-administration of antibiotics with recombinant-PAF-Acetylhydrolase (rPAF-AH) have exhibited promising results. In order to examine the putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Recently, several investigators have reported on the relationship between coagulopathy and proinflammatory events causing organ injury (Abraham 2000 ) (Coughlin 2000 ). Azithromycin has been reported to have immunomodulatory and anti-inflammatory activities, as well as anti-coagulant effects via platelet-activating factor mediated platelet aggregation (Tsoupras et al 2011 ). From the viewpoint of coagulopathy in the pathogenesis of ARDS, azithromycin might have contributed to an improvement in survival in sepsis-associated DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several investigators have reported on the relationship between coagulopathy and proinflammatory events causing organ injury (Abraham 2000 ) (Coughlin 2000 ). Azithromycin has been reported to have immunomodulatory and anti-inflammatory activities, as well as anti-coagulant effects via platelet-activating factor mediated platelet aggregation (Tsoupras et al 2011 ). From the viewpoint of coagulopathy in the pathogenesis of ARDS, azithromycin might have contributed to an improvement in survival in sepsis-associated DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the effects of inflammation on plasma lipids, it is now well established that more important soluble and cellular immune factors associated with chronic inflammation can promote inflammation-related endothelial dysfunction and atherogenesis, either during dyslipidaemia or independently of dyslipidaemia [ 66 ]. Even though atherosclerosis and CVD were previously viewed as lipid storage disorders, we now recognise that inflammation drives much of endothelial dysfunction and mechanisms of clinical complications with these diseases and related comorbidities, such as sepsis [ 67 , 68 ], human immunodeficiency virus (HIV) infection [ 69 , 70 , 71 , 72 , 73 , 74 ], periodontal diseases [ 75 , 76 , 77 ], kidney disorders [ 78 , 79 , 80 , 81 ], healthy ageing, and inflammatory autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis, independently of traditional cardiovascular risk factors such as serum lipid levels [ 66 , 82 , 83 ].…”
Section: Re-discovering Chronic Inflammation As the Cause For Chromentioning
confidence: 99%
“…The most common coexistent diseases associated with chronic infections are CVD, CNS disorders, and tumour malignancies, which are usually promoted by increased levels of PAF and PAF-related continuous and unresolved inflammation [ 57 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 85 , 208 ]. In addition, PAF seems to act in synergy with infectious agents to initiate and propagate the disease process, i.e., viral load in HIV-infected patients was positively correlated with PAF synthesis and levels, while viral products such as Tat-protein induce PAF synthesis and PAF-related HIV-induced non-AIDS comorbidities, such as CVD, Kaposi sarcoma, neurodegeneration, and dementia [ 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: The Role Of Paf In Chronic Diseases and The Beneficial Efmentioning
confidence: 99%
“…24,25 Macrolides have been documented not only to possess adjunctive anti-inflammatory, immunomodulatory activity in vitro, but also to inhibit platelet-activating factor (PAF)-mediated platelet aggregation. 26 Although these activities may underpin the benefits of these agents in the management of CAP, differentiating them from antimicrobial activity in the clinical setting is very difficult. 7…”
Section: Macrolidesmentioning
confidence: 99%
“… decreasing the concentrations of proatherogenic oxLDL-C 42 an inflammatory mediator which promotes platelet activation via interactions with the scavenger receptors LOX-1 and CD36, both of which are expressed on platelets, 43,44 Table 1 summarizes the documented antiplatelet activities of statins, together with those of macrolides, corticosteroids and selective platelet-targeted agents, few of which have been evaluated in CAP. 26,33,42,[45][46][47][48][49][50] We are unaware of any clinically available selective PAF receptor antagonists. Although the activation of proteinase-activated receptor 1 (PAR1, thrombin activated), TxA 2 receptors (TP) and the purinergic receptor, P2Y12 (ADP activated) is largely independent of isoprenylation, the requirement for cholesterol-rich membrane lipid rafts for optimal activity .41 is consistent with possible modulation of these receptors by statins…”
Section: Statinsmentioning
confidence: 99%